Observation of perfect diamagnetism and interfacial effect on the electronic structures in infinite layer Nd0.8Sr0.2NiO2 superconductors - S. W. Zeng; X. M. Yin; C. J. Li; L. E. Chow; C. S. Tang; K. Han; Z. Huang; Y. Cao; D. Y. Wan; Z. T. Zhang; Z. S. Lim; C. Z. Diao; et al. (Nature Communications, 2022)
Nickelate superconductors attract enormous attention in the field of high-temperature superconductivity. Here the authors report observation of perfect diamagnetism and interfacial effect on the electronic structures in infinite layer Nd0.8Sr0.2NiO2 superconductors.